Labor Potential of Country and Regions: Current State and Development Trends - Tereshchenko , Dina (Theory and Practice of Public Administration, 2019)
The global trends of social system transformations and the dynamic nature of the global information space are accompanied by an accelerated development of science and technology, information technologies, and simultaneously, by acute social conflicts, which affects negatively the employment of labor potential and stipulates an increased research interest in the problems of the system transformation of labor potential use under the conditions of forming information economy in the context of meeting social and economic interests of individuals and the society.The paper objective is to explore the current state and the basic trends of employment and development of the labor potential of Ukraine and the country’s regions, to identify the priority areas of the state regulation under the transition towards the innovational principles of economic development.The paper main body. The analysis of the current state of the labor potential of the country and its regions, the characteristic feature of which is aggravation of the negative trends (depopulation; considerable migration losses of the population of the productive age group and that of high professional qualification; worsened health indices in all the age groups; inadequate  sex and age structure of the population; reduction of the birth rate; general aging of the population; low level of remuneration; accelerated migration; impoverishment of the population, etc.) testify to violation of equality of opportunities for people’s development and inconsistency with the priorities of innovation development of the national economy of Ukraine.Conclusions of the research and prospects for further surveys. The problem of devaluation and degrading of the labor potential of the country and its regions requires an immediate solution at the national level, in particular: adoption of the relevant laws aimed at development of new qualitative characteristics of labor potential for application of the knowledge in the economy; elaboration and implementation of effective interrelated state and regional programs which could take into account a considerable difference between the regions; improvement of public administration mechanisms; a change of the dominant social values and  formation of the conditions, prerequisites, and grounds for labor potential development and its employment on the basis of the modernization of social systems and social relations. This, in turn, brings to the forefront the issues of local government development, which would allow bringing closer the solution of the topical socio-economic tasks of labor potential development.A balanced development of the three forms of management, namely: state, private, and social, should become one of the promising areas of forming and employment of the labor potential of the country and its regions. Joint activity of business representatives, authorities, and the social sector in implementing measures aimed to form and realize labor potential will make it possible: to create ample opportunities for the sustainable development at the regional and national levels; to enhance the competitive capacity of the territories; to alleviate inter-regional misbalance; and will promote the advancement of the innovative forms of project management, stimulation of entrepreneurship and demand, as well as solution of the socio-economic problems in Ukraine.